302 Opportunistic assessment of bone mineral density on computed tomography in the gynaecological oncology setting. (13th November 2020) - O'Gorman, C; Milne, S; Lambe, G; Sobota, A; Beddy, P; Gleeson, N
Abstract : Introduction: Women with gynaecological cancers are at increased risk of cancer treatment-induced bone loss(CTIBL). Assessment of bone mineral density(BMD) is recommended internationally prior to commencement of any therapy associated with CTIBL. However, access to DXA is variable. This study explores the utility of assessment of BMD on CTs performed for cancer-staging in the gynaecologic oncology setting. Methods: Prospective, cross-sectional, validation study comparing quantitative BMD assessment on CT(performed at 120kV) to the gold standard, DXA. CT assessment was performed using simple region of interest placement on lumbar vertebral trabecular bone and recording of resultant Hounsfield units(HU). Forty-eight women were included in this study. Results: CT BMD measurement showed significant correlation with DXA diagnostic categories and BMD. AUC for differentiation of normal from abnormally low BMD on CT ranged from 0.75–0.81. Threshold analysis (Youdon's J-statistic) identified the optimal threshold for differentiation of normal from abnormal BMD as 148HU at L3 (sensitivity 82.4%, specificity 83.9%). Conclusion: Assessment of BMD on CT at diagnosis of a gynaecological cancer is simple, differentiates normal from abnormally low BMD with a high degree of accuracy, and requires a negligible increase in reporting time. For this high-risk cohort, it can facilitate early identification of patients with low BMD and optimisation of their bone health prior to deleterious effects of therapy. It can improve prioritisation of DXA referrals and commencement of either therapeutic or prophylactic bone modifying agents as clinically appropriate. The sensitivity and specificity of thresholds should be considered in determining the appropriate threshold for the chosen clinical application.